Dysfunction of Mitochondrial Ca2+ Regulatory Machineries in Brain Aging and Neurodegenerative Diseases - Jung, Hyunsu; Kim, Su Yeon; Canbakis Cecen, Fatma Sema; Cho, Yongcheol; Kwon, Seok-Kyu (Frontiers in Cell and Developmental Biology, 2020)
Calcium ions (Ca2+) play critical roles in neuronal processes, such as signaling pathway activation, transcriptional regulation, and synaptic transmission initiation. Therefore, the regulation of Ca2+ homeostasis is one of the most important processes underlying the basic cellular viability and function of the neuron. Multiple components, including intracellular organelles and plasma membrane Ca2+-ATPase, are involved in neuronal Ca2+ control, and recent studies have focused on investigating the roles of mitochondria in synaptic function. Numerous mitochondrial Ca2+ regulatory proteins have been identified in the past decade, with studies demonstrating the tissue- or cell type-specific function of each component. The mitochondrial calcium uniporter and its binding subunits are major inner mitochondrial membrane proteins contributing to mitochondrial Ca2+ uptake, whereas the mitochondrial Na+/Ca2+ exchanger (NCLX) and mitochondrial permeability transition pore (mPTP) are well-studied proteins involved in Ca2+ extrusion. The level of cytosolic Ca2+ and the resulting characteristics of synaptic vesicle release properties are controlled via mitochondrial Ca2+ uptake and release at presynaptic sites, while in dendrites, mitochondrial Ca2+ regulation affects synaptic plasticity. During brain aging and the progress of neurodegenerative disease, mitochondrial Ca2+ mishandling has been observed using various techniques, including live imaging of Ca2+ dynamics. Furthermore, Ca2+ dysregulation not only disrupts synaptic transmission, but also causes neuronal cell death. Therefore, understanding the detailed pathophysiological mechanisms affecting the recently discovered mitochondrial Ca2+ regulatory machineries will help to identify novel therapeutic targets. Here, we discuss current research into mitochondrial Ca2+ regulatory machineries and how mitochondrial Ca2+ dysregulation contributes to brain aging and neurodegenerative disease.